2016
DOI: 10.1159/000447929
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thyroid Function, Inflammation, and Obesity on Risk Prediction of Acute Kidney Injury by Cystatin C in the Emergency Department

Abstract: Background/Aims: There is a growing role for emergency departments (ED) in assessing acute kidney injury (AKI) for hospital admissions but there are few studies addressing acute kidney injury biomarkers and confounding factors in the ED. Cystatin C (CysC), a newer renal biomarker, is influenced by thyroid function, inflammation and obesity. This study aims to be the first study to address the impact of these parameters in the ED. Methods: Admitted patients (n=397) were enrolled in the ED at Robert-Bosch-Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Therefore, we cannot exclude that cystatinbased eGFR might be affected by inflammatory status, in turn influencing its association with delirium. Yet, in an emergency care setting, where patients with acute inflammatory conditions are referred too, the predictive role of cystatin C as estimate of kidney injury was not negatively affected [50]. Fifth, we were able to adjust data for comorbidity, but not for polypharmacy or pain.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we cannot exclude that cystatinbased eGFR might be affected by inflammatory status, in turn influencing its association with delirium. Yet, in an emergency care setting, where patients with acute inflammatory conditions are referred too, the predictive role of cystatin C as estimate of kidney injury was not negatively affected [50]. Fifth, we were able to adjust data for comorbidity, but not for polypharmacy or pain.…”
Section: Discussionmentioning
confidence: 96%
“…Other formulas, proposed to predict GFR from PCr and other anthropometric data in CKD patients, have not fully validated in severely obese subjects [34, 35]. It is also debated if formulas based on serum cystatin C are more adequate or, to the contrary, may produce a misclassification of CKD stages due to the production of cystatin C by fat cells [36-38]. The inaccuracy in the prediction of UCr from actual body weigth and also from estimated lean body weigth is probably the major cause of error of creatinine based prediction formulas.…”
Section: Discussionmentioning
confidence: 99%
“…However, the receipt of glucocorticoids, thyroid function, inflammation and obesity, rather than sex or age, may affect the measurement of serum CysC[16-18]. Recent studies have further suggested that serum CysC (sCysC) may be an early predictor for AKI and the prognosis of patients in cardiac surgery [19-22], intensive care [23, 24], radiocontrast administration settings [25] and emergency departments [26]. …”
Section: Introductionmentioning
confidence: 99%